Hollow nanometer mullite fiber-based thermal insulation tile material and preparation method thereof
Patent Information
- Application Number
- CN202611399640.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-13
AI Technical Summary
如何平衡中空莫来石纤维基隔热瓦材料的密度、隔热性能和力学性能仍然是一个巨大的挑战
本发明采用在纳米莫来石纤维上通过以PVA与硅溶胶为粘结剂,利用氟化铝催化高活性纳米纤维表面原位生长晶须的方法生成中空纳米莫来石纤维,相较于传统同轴静电纺丝制备中空纤维的方法,本发明无需两套供液系统,操作更简便。同时可避免高温烧除核层时气泡的引入和局部微裂纹的产生,力学性能更佳。
Smart Images

Figure CN122898085A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-temperature resistant ceramic fiber-based heat insulation tile materials, specifically relating to a hollow nano-mullite fiber-based heat insulation tile material and its preparation method. Background Technology
[0002] Oxide ceramic fibers with a high aspect ratio can withstand significant external stress through axial accumulation of localized micro-deformations and can tolerate long-term aerobic environments and high-temperature critical environments. Mullite fiber, as an oxide ceramic fiber filler and matrix material, exhibits excellent high-temperature creep resistance, thermal shock resistance, and corrosion resistance, and is widely used in oily wastewater treatment, gas separation, energy conservation, industrial recycling, and high-temperature insulation. For mullite fiber-based insulation materials, the unique three-dimensional porous structure formed by fiber overlap endows them with high apparent porosity and low bulk density, making them a highly promising ceramic fiber-based insulation tile material.
[0003] Currently, controlling the structure of ceramic fibers is an effective method to improve the thermal insulation performance of ceramic fiber-based thermal insulation tiles. For example, using coaxial electrospinning technology to prepare lightweight hollow nano-ceramic fibers, the inherent hollow structure within the fibers can increase the number of pores in the material and effectively reduce pore size, which is beneficial for synergistically reducing the solid-phase heat conduction and significantly lowering the thermal conductivity. Creating pores on the walls of the hollow fibers using phase inversion methods or by adding pore-forming agents will help reduce density and further lower the thermal conductivity. However, these methods often lead to a decrease in the mechanical properties of fiber-based porous ceramic materials, as the porous walls of the hollow fibers exacerbate the brittleness of materials made from hollow fibers. Balancing the density, thermal insulation performance, and mechanical properties of hollow mullite fiber-based thermal insulation tiles remains a significant challenge. Therefore, providing a multi-level hollow nano-mullite fiber-based thermal insulation tile material with a simple preparation method, low thermal conductivity, and good mechanical properties is of great importance. Summary of the Invention
[0004] The purpose of this invention is to provide a hollow nano-mullite fiber-based thermal insulation tile material and its preparation method. The provided hollow nano-mullite fiber-based thermal insulation tile material exhibits excellent thermal insulation performance. It combines low thermal conductivity and low density, making it suitable for manufacturing high-temperature resistant thermal insulation components, thus providing a lightweight, high-temperature resistant thermal insulation material for aerospace and other fields.
[0005] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for preparing hollow nano-mullite fiber-based heat-insulating tile material, comprising the following steps: A spinning precursor solution was prepared using polymethylhydrosiloxane (PHMS) as the silicon source, aluminum sec-butoxide as the aluminum source, and polyvinylpyrrolidone (PVP) as the spinning aid. Spinning is performed using the aforementioned spinning precursor solution to obtain a precursor fiber membrane; The original fiber membrane was subjected to oxidative crosslinking and pyrolysis to obtain nano-mullite fibers; The nano-mullite fibers were shortened and then mixed with polyvinyl alcohol (PVA) solution, aluminum fluoride (AlF3), silica sol, agarose and water, and heated to obtain ceramic fiber slurry. The ceramic fiber slurry is formed by gel casting, then dried and sintered to obtain the hollow nano-mullite fiber-based heat insulation tile material.
[0006] Preferably, the specific preparation steps of the spinning precursor solution include: preparing solution No. 1 using polymethylhydrosiloxane as the silicon source, preparing solution No. 2 using aluminum sec-butoxide as the aluminum source, and preparing solution No. 3 using polyvinylpyrrolidone as the spinning aid; adding solution No. 1 dropwise to solution No. 2, mixing evenly, and then continuing to add solution No. 3 dropwise, stirring until clear, which is the spinning precursor solution.
[0007] More preferably, solution No. 1 is obtained by mixing isopropanol and polymethylhydrosiloxane at a mass ratio of 1:(0.07-0.095); solution No. 2 is obtained by mixing isopropanol, aluminum sec-butoxide, and ethyl acetoacetate at a mass ratio of 1:(0.6-0.8):(0.4-0.6); and solution No. 3 is obtained by mixing isopropanol, polyvinylpyrrolidone, and N,N-dimethylformamide (DMF) at a mass ratio of 1:(0.2-0.4):(0.1-0.3).
[0008] More preferably, the mass ratio of solution 1, solution 2 and solution 3 is 1:(5.5-7):(7.1-8).
[0009] Preferably, the spinning is electrospinning, and the process parameters of electrospinning are: simultaneous spinning with three needles, accelerating voltage of 8-20kV, receiving distance of 10-20cm, extrusion rate of 0.2-0.6mL / h, and round-trip distance of 60mm.
[0010] Preferably, the oxidative crosslinking is thermal crosslinking in air, and the thermal crosslinking procedure is as follows: starting temperature 50°C, and then increasing the temperature to 160-220°C at a rate of 8-15°C every 15 minutes.
[0011] Preferably, the pyrolysis conditions are as follows: the initial temperature is set at 50°C, and then the temperature is increased to 800°C at a rate of 1 to 5°C / min, and held for 1 to 3 hours.
[0012] Preferably, the shortening operation step includes: placing the nano-mullite fibers in a high-speed homogenizer and working at a speed of 2000-3500 r / min for 2-3 minutes.
[0013] Preferably, the preparation steps of the ceramic fiber slurry include: mixing polyvinyl alcohol solution, aluminum fluoride, silica sol and water evenly and heating; adding agarose when the temperature rises to 82~85℃; adding short-cut nano-mullite fibers when the temperature rises to 86~88℃; and continuing to heat to 88~90℃ for 4~6 minutes to obtain the ceramic fiber slurry.
[0014] More preferably, the polyvinyl alcohol solution has a mass fraction of 3%, the silica sol has a SiO2 content of 40 wt%, and the mass ratio of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water is 1:(0.165~0.660):(0.6~0.8):39.25; the amount of agarose added is 1.0~1.5% of the total mass of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water; and the amount of short-cut nano-mullite fibers added is 2.0~3.0% of the total mass of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water.
[0015] More preferably, the mass ratio of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water is 1:(0.165~0.330):0.75:39.25.
[0016] This mass ratio can effectively balance the thermal insulation and mechanical properties of hollow nano-mullite fiber-based thermal insulation tile materials.
[0017] More preferably, the mass ratio of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water is 1:0.330:0.75:39.25.
[0018] This mass ratio is the optimal ratio that balances the thermal insulation performance and mechanical properties of hollow nano-mullite fiber-based thermal insulation tile materials.
[0019] Preferably, the sintering temperature program is as follows: the initial temperature is 20±10℃, and the temperature is increased sequentially to 800℃, 1000℃, 1200℃ and 1400℃ at a rate of 1~4℃ / min, with each temperature node held for 1~3 hours.
[0020] The second technical solution of the present invention provides a hollow nanomullite fiber-based heat insulation tile material prepared according to the above-mentioned method for preparing hollow nanomullite fiber-based heat insulation tile material.
[0021] The beneficial technical effects of the present invention are as follows: This invention utilizes a method of in-situ growth of whiskers on the surface of highly active nanofibers using PVA and silica sol as binders and catalyzed by aluminum fluoride to generate hollow nanofibers. Compared to the traditional method of preparing hollow fibers by coaxial electrospinning, this invention eliminates the need for two liquid supply systems, making the operation simpler. It also avoids the introduction of bubbles and the generation of local microcracks during high-temperature core layer removal, resulting in superior mechanical properties.
[0022] AlF3 catalyzes the growth of whiskers on the surface of nano-mullite fibers, creating hollow fibers and small-scale voids formed by the overlapping of whiskers on the fiber walls. These voids, together with the inter-fiber pores, form a multi-level porous structure, synergistically reducing solid-phase heat conduction and thus significantly lowering the thermal conductivity, effectively improving the heat insulation performance of fiber-based thermal insulation tiles. Simultaneously, the reduced material density facilitates its participation in the construction of integrated heat insulation material systems.
[0023] Mullite whiskers have the characteristics of high melting point, small coefficient of thermal expansion and high modulus. The fiber wall structure formed by its overlapping has better compressive strength than the wall formed by dense ceramic particles in traditional hollow fibers. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 The images shown are SEM images of the hollow nanomullite fiber-based heat insulation tile material prepared in Example 1; where (a) and (b) are SEM images at different magnifications.
[0026] Figure 2 The images shown are SEM images of the hollow nanomullite fiber-based heat insulation tile material prepared in Example 2; where (a) and (b) are SEM images at different magnifications.
[0027] Figure 3 SEM images of the hollow nanomullite fiber-based thermal insulation tile material prepared in Example 3 are shown; where (a) and (b) are SEM images at different magnifications.
[0028] Figure 4 The images shown are SEM images of the hollow nanomullite fiber-based heat insulation tile material prepared in Example 4; where (a) and (b) are SEM images at different magnifications.
[0029] Figure 5The XRD patterns are of the hollow nanomullite fiber-based heat insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based heat insulation tile materials prepared in Comparative Example 1.
[0030] Figure 6 The volume density and porosity test results of the hollow nanomullite fiber-based heat insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based heat insulation tile materials prepared in Comparative Example 1 are shown.
[0031] Figure 7 The thermal conductivity test results are for the hollow nanomullite fiber-based heat insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based heat insulation tile material prepared in Comparative Example 1.
[0032] Figure 8 The compressive strength and shrinkage rate test results of the hollow nanomullite fiber-based heat insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based heat insulation tile materials prepared in Comparative Example 1 are shown. Detailed Implementation
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0034] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0035] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0036] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0037] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0038] Unless otherwise specified, room temperature in this invention refers to a temperature of 20±10℃.
[0039] The performance testing standards in this embodiment of the invention are as follows: Thermal conductivity: GB / T 10297-2015; Bulk density: GB / T 1966-1996; Porosity: GB / T 1966-1996; Compressive strength: GB / T 1963-1996; Linear shrinkage rate: QB / T 1548-2015.
[0040] Example 1 Multi-level structured whisker-assembled hollow nano-mullite fiber-based heat insulation tile material: Step 1: Mix 1g isopropanol and 0.0846g PHMS at a mass ratio of 1:0.0846 and stir at room temperature for 30 min to obtain solution 1. Mix 3g isopropanol, 2.1g aluminum sec-butoxide, and 1.5g ethyl acetoacetate at a mass ratio of 1:0.7:0.5 and stir at room temperature for 60 min to obtain solution 2. Mix 5g isopropanol, 1.52g PVP, and 1g DMF at a mass ratio of 1:0.304:0.2 and stir at room temperature for 2 h to obtain solution 3. PVP with a weight-average molecular weight of 1,300,000 accounts for 10 wt.% of the mass fraction of the mixed solution (the spinning precursor solution obtained by mixing solutions 1, 2, and 3). After stirring solutions 1 and 2, add solution 1 dropwise to solution 2 and continue stirring for 1 h. After thorough mixing, slowly add the stirred solution No. 3 to the mixture of solutions No. 1 and No. 2, and continue stirring for 9 hours until the solution finally becomes clear and transparent, thus obtaining the spinning precursor solution.
[0041] Step 2: Spin the spinning precursor solution obtained in Step 1 using electrospinning with three needles spinning simultaneously. The spinning conditions are: accelerating voltage 12kV, receiving distance 15cm, extrusion rate 0.4mL / h, round trip distance 60mm, and release paper replaced every 3h to obtain the precursor fiber membrane.
[0042] Step 3: The precursor fiber membrane obtained in Step 2 is first subjected to oxidative crosslinking. The crosslinking conditions are as follows: in an air atmosphere, the initial temperature is set at 50°C, and the temperature is increased by 10°C every 15 minutes until it reaches 200°C.
[0043] Step 4: The cross-linked fiber from Step 3 is subjected to high-temperature pyrolysis. The high-temperature pyrolysis conditions are as follows: under an air atmosphere, the cross-linked and dried fiber membrane is placed in a crucible, the initial temperature is set at 50℃, the temperature is increased to 800℃ at a rate of 2℃ / min, and the temperature is maintained for 2 hours to obtain nano-mullite fiber.
[0044] Step 5: Shorten the mullite nanofibers obtained in Step 4. The shortening conditions are to use a high-speed homogenizer to shorten the mullite nanofibers at a rotation speed of 3000 r / min for 3 min.
[0045] Step 6: Magnetic stirring is performed on 0.2 g of PVA solution (3 wt.%), 0.033 g of AlF3, 0.15 g of silica sol (40 wt% SiO2 content) and 7.85 g of deionized water in a mass ratio of 1:0.165:0.75:39.25. While heating from room temperature to 84°C, 0.1 g of agarose is added in small, repeated additions. When the temperature reaches 88°C, 0.2 g of short-cut nano-mullite fibers is added in small, repeated additions. Stirring continues for 5 minutes after the temperature reaches 89°C to obtain a uniform ceramic fiber slurry.
[0046] Step 7: Quickly pour the ceramic fiber slurry obtained in Step 6 into a square metal mold measuring 2cm × 2cm, and let it stand for 2 hours. Cover with plastic wrap and transfer the metal mold to a refrigerator at 5℃ for 24 hours. Remove the plastic wrap from the mold, disassemble the mold, and obtain the cured wet sample.
[0047] Step 8: Transfer the cured sample wet blank obtained in Step 7 to a forced-air drying oven and hold at 40℃ for 24 hours. Place the completely dried blank into a covered crucible and sinter in an air atmosphere in a high-temperature furnace. The firing regime is as follows: the initial temperature is room temperature, the heating rate is 2℃ / min, and the temperature is raised to 800℃, 1000℃, 1200℃ and 1400℃ and held for 2 hours respectively to obtain hollow nano-mullite fiber-based heat insulation tile material, denoted as S1.
[0048] SEM image of the hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 1 is shown below. Figure 1 As shown, (a) and (b) are SEM images at different magnifications. Figure 1 As can be seen, the generated surface has a fibrous structure with whiskers and a hollow structure.
[0049] The hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 1 was tested for its thermal conductivity, bulk density, porosity, compressive strength, and shrinkage. Its properties were as follows: thermal conductivity at room temperature (25℃) 0.0743 W / (m·K), bulk density 0.252 g / cm³. 3 It has a porosity of 90.21%, a compressive strength of 0.717 MPa, and a shrinkage rate of 4.07%.
[0050] Example 2 Same as Example 1, except that in step 6, the amount of AlF3 added is 0.066g; the resulting hollow nano-mullite fiber-based heat insulation tile material is denoted as S2.
[0051] SEM image of the hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 2 is shown below. Figure 2 As shown, (a) and (b) are SEM images at different magnifications. Figure 2 As can be seen, the material exhibits a hollow fibrous structure formed by well-assembled whiskers, with a smaller whisker aspect ratio than that of the S1 sample.
[0052] The hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 2 was tested for its thermal conductivity, bulk density, porosity, compressive strength, and shrinkage. Its properties were as follows: thermal conductivity at room temperature (25℃) 0.0724 W / (m·K), and bulk density 0.246 g / cm³. 3 It has a porosity of 91.05%, a compressive strength of 0.944 MPa, and a shrinkage rate of 3.52%.
[0053] Example 3 Multi-level structured whisker-assembled hollow nano-mullite fiber-based heat insulation tile material: Step 1: Mix 1g isopropanol and 0.0846g PHMS at a mass ratio of 1:0.0846 and stir at room temperature for 30 min to obtain solution 1. Mix 3g isopropanol, 2.1g aluminum sec-butoxide, and 1.5g ethyl acetoacetate at a mass ratio of 1:0.7:0.5 and stir at room temperature for 60 min to obtain solution 2. Mix 5g isopropanol, 1.52g PVP, and 1g DMF at a mass ratio of 1:0.304:0.2 and stir at room temperature for 2 h to obtain solution 3. Polyvinylpyrrolidone (PVP), with an average molecular weight of 1,300,000, accounts for 10 wt.% of the mass fraction of the mixed solution (the spinning precursor solution obtained by mixing solutions 1, 2, and 3). After the mixtures 1 and 2 are stirred, add solution 1 dropwise to solution 2 and continue stirring for 1 h. After thorough mixing, slowly add the stirred solution No. 3 to the mixture of solutions No. 1 and No. 2, and continue stirring for 7.5 hours until the solution finally becomes clear and transparent, thus obtaining the spinning precursor solution.
[0054] Step 2: Spin the spinning precursor solution obtained in Step 1 using electrospinning with three needles spinning simultaneously. The spinning conditions are: accelerating voltage 10kV, receiving distance 12cm, extrusion rate 0.4mL / h, round trip distance 60mm, and release paper replaced every 3h to obtain the precursor fiber membrane.
[0055] Step 3: The precursor fiber membrane obtained in Step 2 is first subjected to oxidative crosslinking. The crosslinking conditions are as follows: in an air atmosphere, the initial temperature is set at 50°C, and the temperature is increased by 10°C every 15 minutes until it reaches 200°C.
[0056] Step 4: The cross-linked fiber from Step 3 is subjected to high-temperature pyrolysis. The high-temperature pyrolysis conditions are as follows: under an air atmosphere, the cross-linked and dried fiber membrane is placed in a crucible, the initial temperature is set at 50℃, the temperature is increased to 800℃ at a rate of 2℃ / min, and the temperature is maintained for 2 hours to obtain nano-mullite fiber.
[0057] Step 5: Shorten the mullite nanofibers obtained in Step 4. The shortening conditions are to use a high-speed homogenizer to shorten the mullite nanofibers at a speed of 3000 r / min for 3 minutes.
[0058] Step 6: 0.2 g of PVA solution (3 wt.%), 0.099 g of AlF3, 0.15 g of silica sol (40 wt% SiO2 content), and 7.85 g of deionized water are magnetically stirred at a mass ratio of 1:0.495:0.75:39.25. While heating from room temperature to 85°C, 0.1 g of agarose is added in small, repeated additions. When the temperature reaches 88°C, 0.2 g of short-cut mullite nanofibers is added in small, repeated additions. After reaching 89°C, stirring is continued for 6 minutes to obtain a uniform ceramic fiber slurry.
[0059] Step 7: Quickly pour the ceramic fiber slurry obtained in Step 6 into a square metal mold measuring 2cm × 2cm, and let it stand for 2 hours. Cover with plastic wrap and transfer the metal mold to a refrigerator at 5℃ for 30 hours. Remove the plastic wrap from the mold, disassemble the mold, and obtain the cured wet sample.
[0060] Step 8: Transfer the cured sample wet blank obtained in Step 7 to a forced-air drying oven and hold at 40℃ for 24 hours. Place the completely dried blank into a covered crucible and sinter in an air atmosphere in a high-temperature furnace. The firing regime is as follows: the initial temperature is room temperature, the heating rate is 2℃ / min, and the temperature is raised to 800℃, 1000℃, 1200℃ and 1400℃ and held for 2 hours respectively to obtain hollow nano-mullite fiber-based heat insulation tile material, denoted as S3.
[0061] SEM image of the hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 3 is shown below. Figure 3 As shown, (a) and (b) are SEM images at different magnifications. Figure 3 As can be seen, the material exhibits a hollow fibrous structure formed by well-assembled whiskers with the largest aspect ratio of the whiskers.
[0062] The hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 3 was tested for its thermal conductivity, bulk density, porosity, compressive strength, and shrinkage. Its properties were as follows: thermal conductivity at room temperature (25℃) 0.0747 W / (m·K), and bulk density 0.242 g / cm³. 3It has a porosity of 91.38%, a compressive strength of 0.159 MPa, and a shrinkage rate of 2.96%.
[0063] Example 4 Same as Example 1, except that in step 6, the amount of AlF3 added is 0.132g; the resulting hollow nano-mullite fiber-based heat insulation tile material is denoted as S4.
[0064] SEM image of the hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 4 is shown below. Figure 4 As shown, (a) and (b) are SEM images at different magnifications. Figure 4 As can be seen, the hollow fiber structure of the whisker assembly is obvious. Under the induction of aluminum fluoride, the whisker morphology transforms into the lamellar shape of corundum. In addition to the coarsened whiskers, hexagonal lamellar structures are generated on the surface. Both coexist on a single fiber.
[0065] The hollow nano-mullite fiber-based thermal insulation tile material prepared in Example 4 was tested for its thermal conductivity, bulk density, porosity, compressive strength, and shrinkage. Its properties were as follows: thermal conductivity at room temperature (25℃) 0.1177 W / (m·K), and bulk density 0.269 g / cm³. 3 It has a porosity of 88.96%, a compressive strength of 0.222 MPa, and a shrinkage rate of 9.56%.
[0066] Comparative Example 1 Same as Example 1, except that in step 6, the amount of AlF3 added is 0; the resulting nano-mullite fiber-based heat insulation tile material is denoted as S0.
[0067] The XRD patterns of the hollow nanomullite fiber-based thermal insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based thermal insulation tile material prepared in Comparative Example 1 are shown below. Figure 5 .
[0068] Figure 5 The results show that samples S0-S3 are mainly mullite with a very small amount of cristobalite phase; sample S4 has mullite as its main crystalline phase, while also producing a significant amount of corundum phase. Figure 4 The whisker microstructure characteristics of S4 are consistent.
[0069] The bulk density and porosity test results of the hollow nanomullite fiber-based thermal insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based thermal insulation tile material prepared in Comparative Example 1 are shown below. Figure 6 .
[0070] The thermal conductivity test results of the hollow nanomullite fiber-based thermal insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based thermal insulation tile material prepared in Comparative Example 1 are shown below. Figure 7 .
[0071] The compressive strength and shrinkage test results of the hollow nanomullite fiber-based thermal insulation tile materials prepared in Examples 1-4 and the nanomullite fiber-based thermal insulation tile material prepared in Comparative Example 1 are shown below. Figure 8 .
[0072] In summary, this invention reduces the thermal conductivity of mullite fibers by using AlF3 to catalyze the in-situ growth of whiskers on the surface of nano-mullite fibers to form a multi-level porous structure, thereby reducing the solid-phase heat transfer and high-temperature thermal radiation of the fibers. Furthermore, by rationally adjusting the amount of AlF3 added during the gel casting process, the microstructure and thermal insulation performance of hollow nano-mullite fibers can be adjusted and controlled.
[0073] This invention effectively solves the problems of insufficient thermal conductivity and poor strength of existing hollow nano-mullite fiber-based thermal insulation tile materials, and is suitable for high-temperature thermal protection of ultra-high-speed aircraft in aerospace and other fields.
[0074] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a hollow nano-mullite fiber-based heat-insulating tile material, characterized in that, Includes the following steps: A spinning precursor solution was prepared using polymethylhydrosiloxane as the silicon source, aluminum sec-butoxide as the aluminum source, and polyvinylpyrrolidone as the spinning aid. Spinning is performed using the aforementioned spinning precursor solution to obtain a precursor fiber membrane; The original fiber membrane was subjected to oxidative crosslinking and pyrolysis to obtain nano-mullite fibers; The nano-mullite fibers were shortened and then mixed with polyvinyl alcohol solution, aluminum fluoride, silica sol, agarose and water, and heated to obtain ceramic fiber slurry. The ceramic fiber slurry is formed by gel casting, then dried and sintered to obtain the hollow nano-mullite fiber-based heat insulation tile material.
2. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The specific preparation steps of the spinning precursor solution include: preparing solution No. 1 using polymethylhydrosiloxane as the silicon source, preparing solution No. 2 using aluminum sec-butoxide as the aluminum source, and preparing solution No. 3 using polyvinylpyrrolidone as the spinning aid; adding solution No. 1 dropwise to solution No. 2, mixing evenly, and then continuing to add solution No. 3 dropwise, stirring until clear, which is the spinning precursor solution.
3. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 2, characterized in that, Solution 1 is obtained by mixing isopropanol and polymethylhydrosiloxane at a mass ratio of 1:(0.07-0.095); Solution 2 is obtained by mixing isopropanol, aluminum sec-butoxide, and ethyl acetoacetate at a mass ratio of 1:(0.6-0.8):(0.4-0.6); Solution 3 is obtained by mixing isopropanol, polyvinylpyrrolidone, and N,N-dimethylformamide at a mass ratio of 1:(0.2-0.4):(0.1-0.3); and / or, the mass ratio of Solution 1, Solution 2, and Solution 3 is 1:(5.5-7):(7.1-8).
4. The preparation method of the hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The spinning is electrospinning, and the process parameters for electrospinning are: simultaneous spinning with three needles, accelerating voltage of 8-20kV, receiving distance of 10-20cm, extrusion rate of 0.2-0.6mL / h, and round-trip distance of 60mm.
5. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The oxidative crosslinking is thermal crosslinking in air, and the thermal crosslinking procedure is as follows: starting temperature 50°C, and then increasing the temperature to 160-220°C at a rate of 8-15°C per 15 min; and / or, the pyrolysis conditions are as follows: starting temperature set at 50°C, and then increasing the temperature to 800°C at a rate of 1-5°C / min, and holding at that temperature for 1-3 h.
6. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The shortening operation includes: placing the nano-mullite fibers in a high-speed homogenizer and working at a speed of 2000-3500 r / min for 2-3 minutes.
7. The method for preparing hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The preparation steps of the ceramic fiber slurry include: mixing polyvinyl alcohol solution, aluminum fluoride, silica sol and water evenly and heating; adding agarose when the temperature rises to 82~85℃; adding short-cut nano-mullite fibers when the temperature rises to 86~88℃; and continuing to heat to 88~90℃ for 4~6 minutes to obtain the ceramic fiber slurry.
8. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 7, characterized in that, The polyvinyl alcohol solution has a mass fraction of 3%, the silica sol has a SiO2 content of 40 wt%, and the mass ratio of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water is 1:(0.165~0.660):(0.6~0.8):39.25; the amount of agarose added is 1.0~1.5% of the total mass of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water; and the amount of short-cut nano-mullite fibers added is 2.0~3.0% of the total mass of the polyvinyl alcohol solution, aluminum fluoride, silica sol, and water.
9. The method for preparing the hollow nano-mullite fiber-based heat-insulating tile material according to claim 1, characterized in that, The sintering temperature program is as follows: the initial temperature is 20±10℃, and the temperature is increased sequentially to 800℃, 1000℃, 1200℃ and 1400℃ at a rate of 1~4℃ / min, with each temperature node held for 1~3 hours.
10. A hollow nanomullite fiber-based heat insulation tile material prepared by the method of preparing hollow nanomullite fiber-based heat insulation tile material according to any one of claims 1 to 9.